Rhetorical criticism of Baul Lalon Shah’s Songs: A Perspective on Humanity - Azad, Abul Kalam; Ahmad, Abdul Mua’ti @Zamri; Waheed, Moniza; Zainudin, Sharifah Sofiah Syed (Journal of Ecohumanism, 2024)
This article explores the songs of Baul Lalon Shah, a prominent figure in the classical folklore of 19th-century Bengal under British rule. Lalon’s music, deeply rooted in humanism, transcends caste, religion, and social divisions, emphasizing unity, equality, and peace. As a member of the Baul community, Lalon integrated diverse religious philosophies, including Hinduism, Tantric Buddhism, and Sufi Islam, into a unique spiritual discourse centred on humanity. His songs advocate for the primacy of humanism over religious and societal binaries. Despite their profound philosophical contributions, Lalon’s songs have not been analyzed using rhetorical methods thoroughly. This study seeks to fill that gap by applying rhetorical analysis to examine the humanistic philosophy embedded in Lalon Shah’s works. By doing so, it aims to reveal the enduring significance of his message in Bengali society and contribute to the broader discourse on global humanism. Disseminating these insights can play a transformative role in cultural and philosophical spheres.